2020
DOI: 10.3390/plants9020182
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar Resistance against Colletotrichum asianum in the World Collection of Mango Germplasm in Southeastern Brazil

Abstract: During the spring of 2014, a wide survey was conducted in one of the most important mango (Mangifera indica) cultivating areas located in Minas Gerais State (Brazil) to ascertain the causal agent of severe anthracnose infections and to evaluate disease susceptibility within a world collection of mango germplasm. Overall, 86 cultivars were monitored and 152 fungal isolates recovered from infected samples were identified by morphological characterization, DNA sequencing and phylogenetic analyses. All isolates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…In the present study, the anthracnose pathogen can result in dark lesions in the fruit, calyx, branches, and leaf of persimmon, showing similar results with previous reports [9,15,22,30]. In addition, the C. gloeosporioides species complex consists of important plant pathogens that can cause anthracnose in economic crops, such as chili [31], mango [32], strawberry [33], apples [34], grapes [35], bananas [36,37], and tomato [38]. As a destructive disease of persimmon trees, C. horii can cause leaf defoliation, fruit rot, and even the death of the whole plant [39].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the anthracnose pathogen can result in dark lesions in the fruit, calyx, branches, and leaf of persimmon, showing similar results with previous reports [9,15,22,30]. In addition, the C. gloeosporioides species complex consists of important plant pathogens that can cause anthracnose in economic crops, such as chili [31], mango [32], strawberry [33], apples [34], grapes [35], bananas [36,37], and tomato [38]. As a destructive disease of persimmon trees, C. horii can cause leaf defoliation, fruit rot, and even the death of the whole plant [39].…”
Section: Discussionsupporting
confidence: 91%
“…C. fructicola has been reported as a causal agent of fruit anthracnose in apple (VELHO et al 2015), grapes (ECHEVERRIGARAY et al, 2020), and other crop fruits in Brazil, and was first reported in persimmon in Parana State (Southern Brazil) by CARRARO et al (2019), and C. aenigma was previously associated to sweet persimmon anthracnose in Korea (HASSAN et al, 2018), and grape ripe-rot disease in Southern Brazil (ECHEVERRIGARAY et al, 2020). Moreover, C. asianum is associated with anthracnose in coffee (PRIHASTUTI et al, 2009) and mango (SHARMA et al, 2015, VITALE et al, 2020, but this is the first report of this species on persimmon.…”
Section: Resultsmentioning
confidence: 88%
“…In the post-hoc analysis, the mean separation was conducted on all variables using post-hoc Fisher's least significant difference test at α = 0.05. Prior to analysis, percentage values were transformed as arcsine square root (sin −1 square root x) to improve homogeneity of variances [47].…”
Section: Discussionmentioning
confidence: 99%